Formation and influence factors of halonitromethanes in chlorination of nitro-aromatic compounds. (September 2021) - Wang, Junjie; Li, Zhigang; Hu, Shaoyang; Ma, Jian; Gong, Tingting; Xian, Qiming
Abstract: Halonitromethanes (HNMs), typical nitrogenous disinfection byproducts generated during disinfection of chlorination and chloramination, are widely detected in drinking water. This study investigated the formation of two dominant HNMs, trichloronitromethane (TCNM) and dichloronitromethane (DCNM) during chlorination/chloramination of ten nitro-aromatic compounds (NACs), including six aromatic mono-nitro compounds, three aromatic di-nitro compounds and one aromatic tri-nitro compound. The results showed that 2-nitrophenol and 3-nitrophenol could be the main precursors of TCNM and DCNM, and the yields of TCNM were one order of magnitude higher than that of DCNM. HNMs formation in chlorination was much higher than that in chloramination. However, HNMs were hardly produced during chlorination and chloramination of the other eight NACs. In chlorination of 2-nitrophenol, a pH range of 5.0–7.0 facilitated the TCNM formation. Besides, the concentration of ferric and manganese ions had different influences on TCNM formation. While the concentration ranges were 0–2 mg/L, ferric ion significantly decreased TCNM formation but manganese ion had not any influence on TCNM formation. Contrary to a previous finding, nitrite significantly reduced TCNM formation, which implied that nitrite has different effects on TCNM formation from various precursors. Moreover, dissolved organic matter (DOM, 0–5 mg/L as C) significantly influenced the formation of TCNM in chlorination of 2-nitrophenol despite the low TCNM formation in chlorination of DOM. Several chlorinated intermediates were detected and identified as mono/di/tri-chloro-2-nitrophenol during chlorination of 2-nitrophenol. It is effectively to reduce the production of TCNM and DCNM formation from chlorination of 2-nitrophenol by controlling disinfection conditions in drinking water. Graphical abstract: Image 1 Highlights: 2/3-nitrophenol is the main precursors of HNMs formation for nitro-aromatic compounds. Chloramination significantly reduced the formation potential of TCNM and DCNM. Ions had different effects on the formation of TCNM and DCNM in chlorination of 2-nitrophenol. The formation pathways of HNMs from chlorination of 2-nitrophenol were tentatively proposed.